An improved empirical model of electron and ion fluxes at geosynchronous orbit based on upstream solar wind conditions. Issue 7 (27th July 2016) - Denton, M. H.; Henderson, M. G.; Jordanova, V. K.; Thomsen, M. F.; Borovsky, J. E.; Woodroffe, J.; Hartley, D. P.; Pitchford, D.
Abstract: A new empirical model of the electron fluxes and ion fluxes at geosynchronous orbit (GEO) is introduced, based on observations by Los Alamos National Laboratory (LANL) satellites. The model provides flux predictions in the energy range ~1 eV to ~40 keV, as a function of local time, energy, and the strength of the solar wind electric field (the negative product of the solar wind speed and the z component of the magnetic field). Given appropriate upstream solar wind measurements, the model provides a forecast of the fluxes at GEO with a ~1 h lead time. Model predictions are tested against in‐sample observations from LANL satellites and also against out‐of‐sample observations from the Compact Environmental Anomaly Sensor II detector on the AMC‐12 satellite. The model does not reproduce all structure seen in the observations. However, for the intervals studied here (quiet and storm times) the normalized root‐mean‐square deviation < ~0.3. It is intended that the model will improve forecasting of the spacecraft environment at GEO and also provide improved boundary/input conditions for physical models of the magnetosphere. Key Points: New model of electron and ion fluxes at GEO (driven by ‐ vB z ) provides a ~1 h forecast of fluxes in the energy range ~1 eV to ~40 keV The main benefit from the new model is the ability to predict the fluxes at GEO in advance Forecasts are a good match to observations during quiet times and storm times